Experiences of therapeutic relationships on hospital wards, dissociation, and making connections. Issue 4 (8th August 2017) - Parry, Sarah; Lloyd, Mike; Simpson, Jane
ABSTRACT: An interpretive phenomenological analysis sought to explore how people reporting moderate to high levels of dissociation experienced relationships with multidisciplinary hospital ward staff. Three superordinate themes were developed. First, the theme "multiple me and multiple them" explores the instability experienced by the participants as they managed their dissociative experiences alongside many inconsistencies. Second, "recognizing, meeting, or neglecting interpersonal and care needs" reflects on participants' needs within therapeutic relationships. Third, "between the needs of the internal system: navigating between 'better on my own' and 'someone to talk to'" discusses the confusion and understanding around dissociation and the importance of working with parts, not around them. Findings suggested that the current culture of some hospital wards directly influenced participants' distress, which could lead to further dissociation as a means of coping with perceived threats. Reflections on relational complexities and developing ward-based treatment are discussed.